A Thrombocytopenic Thrombotic Purpura in a Patient With a Metastatic HER2+ Breast Cancer: Description of a Case Report - Raffaele Longo; Benjamin Savenkoff; Romane Ribal; Alexandre Dadoun; Marco Campitiello; Francesca Plastino; Pierre‐Olivier Legros; Nathalie Marcon; Paul Coppo; Julie Egea (Clinical Case Reports)
ABSTRACT Paraneoplastic (p) TTP is a rare syndrome characterized by an immune‐induced, generalized microangiopathy associated with solid or hematological tumors. This case, reporting a patient with a metastatic HER2+ breast cancer and a pTTP, highlights the rarity of this entity, its difficult and challenging diagnosis, and the complexity of its management.